Work for a brighter future : Global Commission for the Future of Work. - International Labour Organization (Geneva : International Labour Organization, 2019)
This landmark report by the ILO Global Commission on the Future of Work examines how to achieve a better future of work for all at a time of unprecedented change and exceptional challenges in the world of work.
2.3 Increasing investment in decent and sustainable work -- Transforming economies to promote decent and sustainable work -- Shifting incentives: Towards a human-centred business and economic model -- 3. Taking responsibility -- Reinvigorating the social contract -- The responsibilities of the ILO -- Responsibilities and challenges of the multilateral system -- Final comment -- Notes -- Bibliography -- Annex. Members of the Global Commission on the Future of Work
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed April 26, 2022).
eBooks on EBSCOhost
Keywords: Work -- Forecasting; Travail -- Prévision.; Work -- Forecasting